Precipitation of CsPbBr3 quantum dots in borophosphate glasses inducted by heat-treatment and UV-NIR ultrafast lasers - Du, Ying; Wang, Xin; Shen, Danyang; Yuan, Jun; Wang, Yajie; Yan, Sasa; Han, Shuai; Tao, Yiting; Chen, Danping (Chemical engineering journal (Lausanne, Switzerland : 1996), 2020)
•CsPbBr3 QDs glasses were fabricated by heat-treatment and UV-NIR ultrafast lasers.•CsPbBr3 QDs glasses exhibited excellent luminescence and behaved good stabilities.•The laser-induced crystallization on glass surface and interior is very different.•The grain size of QDs on glass surface by lasers decreased after heat-treatment.•The CsPbBr3 crystal nuclei inside glasses by lasers grew up through heat-treatment. Low-melting borophosphate glasses were fabricated via melt-quenching and then CsPbBr3 quantum dots (QDs) were synthesized in the glasses by heat-treatment and UV-NIR ultrafast lasers irradiation. CsPbBr3 QDs embedded glasses obtained by heat-treatment were confirmed by X-ray diffraction patterns, TEM images and spectral analyses and behaved excellent thermal and moisture stabilities. Moreover, the behavior of lasers-induced crystallization on the surface and interior of glasses is greatly different. CsPbBr3 QDs could directly be precipitated on the surface of glasses by using low peak power ultrafast lasers irradiation and the subsequent heat-treatment would lead to the reduction of nanocrystalline size because there are defects and crystal nucleuses on the surface of glasses. However, the irradiation of high peak power ultrafast lasers could only nucleate inside glass because of the lack of nucleation points inside glasses and the subsequent heat-treatment was required to precipitate CsPbBr3 QDs. The higher the peak power of ultrafast lasers, the stronger the luminescence intensity of CsPbBr3 QDs and the longer its fluorescence lifetime.